Public Financial Management in Education and Youth Affairs: A Systematic Literature Review of Key Challenges for Sustainable Development and Policy Implementation - Randy Lieminarto; Sarwani Sarwani; Ulul Albab (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Public Financial Management (PFM) is a critical element of good governance, transparency, and accountability, with direct implications for education and youth development. Despite its significance, research on PFM in these sectors remains fragmented, limiting a holistic understanding of its impact. This study conducts a Systematic Literature Review (SLR) to synthesize existing scholarship on PFM in education and youth affairs, following the PRISMA 2020 guidelines. A comprehensive search across Scopus and Web of Science identified peer-reviewed studies addressing financial governance, budgeting practices, accountability mechanisms, and financial literacy programs. The findings reveal that effective PFM contributes to improved educational outcomes by enhancing financial literacy, ensuring timely budget disbursement, promoting student savings, and enabling equitable access to financial education. Conversely, persistent challenges such as delays in fund allocation, weak accountability, and disparities in program implementation continue to hinder progress. The review also highlights the broader implications of SLRs in advancing curriculum innovation, guiding evidence-based policymaking, and strengthening accountability frameworks in education finance. This study contributes to both theory and practice by offering an integrated synthesis of PFM in education and youth affairs, identifying critical research gaps, and providing recommendations for policymakers and practitioners. The results underscore the importance of embedding financial literacy into school curricula, adopting performance-based budgeting, and fostering collaboration between researchers and policymakers. Ultimately, strengthening PFM in education not only enhances institutional efficiency but also equips youth with the financial skills and opportunities required for sustainable social and economic development The findings from this review contribute to the ongoing discourse on PFM by offering an integrated synthesis of current knowledge. The study not only uncovers critical research gaps but also provides actionable recommendations for both policymakers and practitioners.